Evaluation of the patient exposure dose during ERCP Fluoroscopy guided procedures - Granadas, Marisa (2022)
Endoscopic retrograde cholangiopancreatography (ERCP) is a diagnostic/therapeutic fluoroscopy guided procedure that includes upper gastrointestinal endoscopy allowing the treatment of the bile and pancreatic ducts pathologies. Currently, ERCP is mostly used in therapy, which turns in to longer procedures, with potential higher doses of ionizing radiation to the patient and due to the cancer development risk it's relevant to evaluate dose exposure during ERCP. The International Atomic Energy Agency (IAEA) defined the mean dose area product (DAP) for ERCP diagnostic procedures as 15 Gy.cm2 and mean...